A novel coculture model of porcine central neuroretina explants and retinal pigment epithelium cells - Di Lauro, Salvatore (Mol Vis, 2016)
PURPOSE: To develop and standardize a novel organ culture model using porcine central neuroretina explants and RPE cells separated by a cell culture membrane. METHODS: RPE cells were isolated from porcine eyes, expanded, and seeded on the bottom of cell culture inserts. Neuroretina explants were obtained from the area centralis and cultured alone (controls) on cell culture membranes or supplemented with RPE cells in the same wells but physically separated by the culture membrane. Finally, cellular and tissue specimens were processed for phase contrast, cyto-/histological, and immunochemical evaluation. Neuroretina thickness was also determined. RESULTS: Compared to the neuroretinas cultured alone, the neuroretinas cocultured with RPE cells maintained better tissue structure and cellular organization, displayed better preservation of photoreceptors containing rhodopsin, lower levels of glial fibrillary acidic protein immunoexpression, and preservation of cellular retinaldehyde binding protein both markers of reactive gliosis. Neuroretina thickness was significantly greater in the cocultures. CONCLUSIONS: A coculture model of central porcine neuroretina and RPE cells was successfully developed and standardized. This model mimics a subretinal space and will be useful in studying interactions between the RPE and the neuroretina and to preclinically test potential therapies.